A novel blood pressure monitoring technique by smart HUAWEI WATCH: A validation study according to the ANSI/AAMI/ISO 81060-2:2018 guidelines - Wang, Lili; Xian, Hong; Guo, Jiajun; Li, Weihao; Wang, Jiaqi; Chen, Qing; Fu, Xiaoyu; Li, Hongbao; Chen, Qin; Zhang, Wei; Chen, Yucheng (Frontiers in Cardiovascular Medicine, 2022)
Background Given the rapid innovation of wearable technology, additional physical indicators can be detected, and blood pressure (BP) has become the focus of many emerging medical-device manufacturers. This study aimed to validate the accuracy of the newly developed HUAWEI WATCH in BP monitoring, according to the American National Standards Institute/Association for the Advancement of Medical Instrumentation/International Organization for Standardization (ANSI/AAMI/ISO 81060-2:2018) guidelines. Materials and methods The same arm sequential BP measurement was applied. One validation included four reference BP measurements taken simultaneously by two independent observers using a mercury sphygmomanometer, alternating with three test-watch measurements. Each test-watch measurement was compared against the average of the previous and subsequent reference BP readings. Two criteria were required for validation: (1) a mean BP difference of 5 mm Hg or less, with a standard deviation (SD) of 8 mm Hg or less for systolic blood pressure (SBP) and diastolic blood pressure (DBP) in the 255 pairs of measurements, and (2) an SD for the of 85 averaged BP differences within the threshold defined by the mean test-reference BP difference listed in the ANSI/AAMI/ISO 81060-2:2018 guidelines. Results The mean age of the 85 participants was 48 ± 18 years (range: 21–85), and 53 (62.4%) were male. The mean differences between the test and reference BPs were -0.25 ± 5.62 mm Hg and -1.33 ± 6.81 mm Hg for SBP and DBP, respectively (according to Criterion 1). The mean differences between the test BPs and reference BPs were -0.25 ± 5.00 mm Hg and -1.33 ± 6.31 mm Hg for SBP and DBP, respectively, according to Criterion 2. Conclusion Blood pressure measurement using the HUAWEI WATCH showed excellent consistency with reference BPs, and fulfilled both validation criteria of the guidelines, show its promise as a wearable device for BP self-monitoring.